1997
DOI: 10.1029/96jc02776
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic, quasi‐hydrostatic, and nonhydrostatic ocean modeling

Abstract: Abstract. Ocean models based on consistent hydrostatic, quasi-hydrostatic, and nonhydrostatic equation sets are formulated and discussed. The quasi-hydrostatic and nonhydrostatic sets are more accurate than the widely used hydrostatic primitive equations. Quasi-hydrostatic models relax the precise balance between gravity and pressure gradient forces by including in a consistent manner cosine-of-latitude Coriolis terms which are neglected in primitive equation models. Nonhydrostatic models employ the full incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
735
1
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,221 publications
(750 citation statements)
references
References 28 publications
6
735
1
8
Order By: Relevance
“…This is consistent with the schematic provided in Fig. 2 and with laboratory and numerical experiments (Narimousa 1998;Marshall and Schott 1999). The cyclone mostly contains water from outside the initial mixed patch.…”
Section: A Mixed-patch Releasesupporting
confidence: 76%
See 2 more Smart Citations
“…This is consistent with the schematic provided in Fig. 2 and with laboratory and numerical experiments (Narimousa 1998;Marshall and Schott 1999). The cyclone mostly contains water from outside the initial mixed patch.…”
Section: A Mixed-patch Releasesupporting
confidence: 76%
“…For this reason, mixed-patch release experiments were carried out in a simple channel setting as well as in basin experiments more closely representing the Greenland Sea. All experiments were carried out with the Massachusetts Institute of Technology general circulation model (MITgcm; Marshall et al 1997) on an f plane ( f ϭ 1.5 ϫ 10 Ϫ4 s Ϫ1 ). The vertical resolution of the 40 levels decreased from 11 m at the surface to 147 m at the bottom (3750 m), and a very high horizontal resolution of 500 m ϫ 500 m was applied in order to resolve postconvective vortices.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same experiment was also conducted using the Massachusetts Institute of Technology general circulation model (MITgcm) and the Bergen Ocean Model (BOM) by Berntsen et al [2006]. MITgcm is a z coordinate structured grid nonhydrostatic finite volume model that uses a shaved cell approach to treat near-bottom flow over sloping-bottomed topography [Marshall et al, 1997a[Marshall et al, , 1997b, and BOM is a sigma coordinate nonhydrostatic finite difference model [Berntsen, 2000]. Berntsen et al [2006] found that the shoaling and breaking process predicted by MITgcm in the case without bottom friction looked like BOM's results with bottom friction.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…FVCOM was developed originally with the hydrostatic approximation in which the rate of change, advection, and diffusion of the vertical velocity are ignored and the pressure gradient in the vertical is balanced by gravity. According to scaling analysis, the hydrostatic balance is valid for large-scale motions in regional scale and larger-scale ocean waters, where the horizontal motion is dominant [Mahadevan et al, 1996a;Marshall et al, 1997a]. In coastal and estuarine waters, particularly over shallow banks and the shelfbreak where internal waves can be energetic, and in inlets or narrow river passages, where the motion's horizontal scale can be comparable to the local depth, the flow is influenced by nonhydrostatic dynamics.…”
Section: Introductionmentioning
confidence: 99%